PRARANCANGAN PABRIK FENOL DARI KUMEN HIDROPEROKSIDA DAN KATALIS ASAM SULFAT DENGAN PROSES DEKOMPOSISI KUMEN HIDROPEROKSIDA KAPASITAS 60.000 TON/TAHUN - SYAHAB, MUHAMMAD, Tri Widayatno,S.T., MS.c., Ph.D, Hamid Abdillah, S.T., M.T (2015)
Phenol is a chemical in the industry are included in the class hydrobenzen.Fenol widely used in industry, especially phenolic resin industry, the manufacture of bisphenol-A, the plastics industry, and so forth. Phenol needs in Indonesia tends to increase every year. Therefore, the establishment of a phenol plant in Indonesia is very important to reduce imports. Phenol plant is expected to meet domestic needs and it is possible to export. The process of making phenol done dekomoposisi cumen hydroperoxide with sulfuric acid catalyst. Dekomoposisi kumen hydroperoxide run at continuous stirred tank reactor (CSTR) with a temperature of 65oC operating conditions and pressure of 2 atm. Exothermic reaction in the reactor. The main byproducts of this process is acetone. Purification of the product is done by a process of distillation, in order to obtain a product with a purity of 99.9%. Phenol plant is designed with a capacity of 60,000 tons / year in operation for 330 days / year. Phenol plant requires raw materials kumen hydroperoxide (CHP) as much as 110,001.44 tons / year, and sulfuric acid as much as 395.00 tons / year. Unit utility as supporting the production process requires as much water as 35.914,076kg / hr is taken from the river Cisadene, saturated steam as 37.347,86kJ / h obtained from the boiler with diesel fuel as much as 4.25 liters / hour, the needs of 73.701 kW electrical power is supplied PLN and generator set as a backup, and the compressed air requirements of 101.52 m3 / h. From the economic analysis, phenol plant requires fixed capital (fixed capital) amounted to Rp. 369.400.804.196,96dan working capital (working capital) amounted to Rp. 775,067,521,406.41. Profits earned before tax of Rp. 230,727,007,195.05 annually. Profit after tax of Rp. 161,508,905,036.54 annually. Results of a feasibility analysis stated that the percent return on investment (ROI) before tax of 62.46% and after tax of 43.73%. Pay out time (POT) before tax of 1.38 years, while after tax of 1.86 years. Break even point (BEP) amounted to 51.31% of capacity, and shut down point (SDP) amounted to 41.96% of capacity. Discounted cash flow (DCF) by 38%. Based on the analysis with these parameters, the phenol plant is feasible to set up in Indonesia.